Nurses’ Knowledge and Attitudes toward Pacemaker: A Cross-Sectional Study: Pengetahuan dan Sikap Perawat terhadap Alat Pacu Jantung: Sebuah Studi Cross-Sectional - Ali Malik Tiryag (Universitas Muhammadiyah Sidoarjo, 2024)
Despite the critical role of pacemakers in managing symptomatic atrioventricular and ventricular conduction abnormalities, there remains a significant gap in the knowledge and attitudes of nurses towards these devices. This study assesses the understanding and perceptions of pacemakers among nurses in Al-Basrah Governorate hospitals, exploring associations with demographic factors such as age, gender, educational level, years of experience, and training. Employing a descriptive methodology, a non-probability sample of 200 nurses from five hospitals (Abi Al-Khasib General Hospital, Umm Qasr General Hospital, Al-Zubair General Hospital, Al-Shifaa Hospital, and Al-Mawani Teaching Hospital) was surveyed from October 15, 2022, to August 15, 2023. Content validity was ensured by engaging eleven professionals, while reliability was assessed using Cronbach's Alpha. Results indicate a concerning deficiency in pacemaker-related knowledge, with 79.5% of nurses demonstrating poor knowledge, 18% showing intermediate knowledge, and only 2.5% exhibiting high knowledge. Similarly, attitudes were predominantly negative, with 81.5% of nurses expressing low enthusiasm towards pacemakers, while 11% and 7.5% displayed intermediate and high attitudes, respectively. These findings highlight the need for targeted educational interventions aimed at enhancing nurses' competence and attitudes concerning pacemakers to improve postoperative care and management outcomes for patients with these devices. Highlights: Knowledge Gap: A significant 79.5% of nurses show insufficient knowledge of pacemakers, indicating a critical need for improved medical education. Attitudinal Barriers: Over 81% of nurses have negative attitudes towards pacemakers, which may affect patient care quality. Training Requirement: There's a clear need for specialized training programs for nurses on pacemakers to enhance their knowledge and attitudes, ultimately improving patient care. Keywords: Pacemaker Knowledge, Nursing Attitudes, Educational Interventions